2010
DOI: 10.1186/1475-2875-9-171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a rapid diagnostic test (CareStart™ Malaria HRP-2/pLDH (Pf/pan) Combo Test) for the diagnosis of malaria in a reference setting

Abstract: BackgroundMalaria Rapid Diagnostic Tests (RDTs) are widely used for diagnosing malaria. The present retrospective study evaluated the CareStart™ Malaria HRP-2/pLDH (Pf/pan) Combo Test targeting the Plasmodium falciparum specific antigen histidine-rich protein (HRP-2) and the pan-Plasmodium antigen lactate dehydrogenase (pLDH) in a reference setting.MethodsThe CareStart™ Malaria HRP-2/pLDH (Pf/pan) Combo Test was evaluated on a collection of samples obtained in returned international travellers using microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
100
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 30 publications
14
100
4
Order By: Relevance
“…The sensitivity (99.7%) that we report here for the CareStart Malaria Pf/Pv Combo Test to detect P. falciparum species was comparable with the sensitivity findings reported as 99.4% in Wondogenet, 14 98% in Uganda, 21 and 96.91% in Karachi, 16 but our finding was higher than the reports of 88.8% in Belgium, 13 89.1% in Myanmar, 22 and 88.52% in ChinaMyanmar. 19 Because the parasite density in the present study was greater than 100 parasites/μL blood, which was shown in the microscopic examination of thick film, the sensitivity was higher.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The sensitivity (99.7%) that we report here for the CareStart Malaria Pf/Pv Combo Test to detect P. falciparum species was comparable with the sensitivity findings reported as 99.4% in Wondogenet, 14 98% in Uganda, 21 and 96.91% in Karachi, 16 but our finding was higher than the reports of 88.8% in Belgium, 13 89.1% in Myanmar, 22 and 88.52% in ChinaMyanmar. 19 Because the parasite density in the present study was greater than 100 parasites/μL blood, which was shown in the microscopic examination of thick film, the sensitivity was higher.…”
Section: Discussionsupporting
confidence: 84%
“…19 Because the parasite density in the present study was greater than 100 parasites/μL blood, which was shown in the microscopic examination of thick film, the sensitivity was higher. This type of relationship between parasite density and RDT performance has also been indicated earlier, 13 showing that, when the parasite load is 100 parasites/μL, the performance of CareStart will be high. However, the sensitivity of the RDT is low when the parasite density is below 100 parasites/μL blood (mostly in asymptomatic cases).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The sensitivity of the RDT in the current study for P. falciparum corresponded with the reports by Bruno B Andrade et al (20). The sensitivity of the RDT in the current study for P. falciparum was also higher than Maltha et al, (21) and lower than China Myanmar endemic borders (17), Indonesia (22) and Jimma, as well as southwest Ethiopia (14). The specificity of the RDT in the present study for P. falciparum was similar to the reports from Jimma, southwestern Ethiopia (14), and higher than the reports from southern (23) and Ethiopia and Madagascar (15,24).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the association between false-negative RDTs and a low MOI suggests that this discrepancy may become increasingly important as malaria control becomes more effective. Based on these results, we suggest that the RDTs used to diagnose P. falciparum infection in humans should target parasite proteins thought to be essential (e.g., parasite lactic dehydrogenase) 1,[27][28][29] and should also consider proteins with identifiable (distinguishable) variants in other plasmodial species. hrp2 PCR results for smear-positive specimens with negative vs. positive HRP2-based RDT results.…”
Section: Discussionmentioning
confidence: 97%